Development of the Apide Supervision Process for Internal Quality Assurance of Schools Under the Nakhon Si Thammarat Primary Educational Service Area Office 2: Development of the Apide Supervision Process for Internal Quality Assurance of Schools Under the Nakhon Si Thammarat Primary Educational Service Area Office 2 - Promvihan, Ornanong (RATANABUTH JOURNAL, 2026)
The purposes of this research were to: (1) develop the APIDE supervision process for the internal quality assurance of educational institutions under the Nakhon Si Thammarat Primary Educational Service Area Office 2, and (2) evaluate the implementation of the developed process. The study consisted of two phases. Phase 1 focused on the development of the APIDE supervision process. The sample included 372 teachers responsible for internal quality assurance at both the early childhood and basic education levels, together with five experts selected through purposive sampling. The research instruments were a questionnaire on the current state of internal quality assurance implementation and an evaluation form for the APIDE supervision process. Data were analyzed using the mean and standard deviation. Phase 2 evaluated the implementation of the APIDE supervision process. The sample consisted of 186 teachers responsible for internal quality assurance who voluntarily participated in the development program. The research instruments included a knowledge test on internal quality assurance, an internal quality assurance system evaluation form, an internal and external quality assessment record form, and a satisfaction questionnaire. Data were analyzed using percentage, mean, standard deviation, and paired-samples t-test. The findings revealed that the APIDE supervision process comprised five stages: Analysis (A), Planning (P), Informing (I), Doing (D), and Evaluating (E). The experts rated the process at a high level in terms of appropriateness, feasibility, utility, and accuracy. After implementing the APIDE supervision process, teachers’ knowledge and understanding of internal quality assurance were significantly higher than before the implementation at the .05 level. The overall implementation of the internal quality assurance system was rated at a high level (= 4.74, S.D. = 0.37). The results of both internal and external quality assessments at the early childhood and basic education levels showed an improving trend, with most educational institutions achieving an Excellent level or above. Teachers’ overall satisfaction with the APIDE supervision process was also at a high level (= 4.46, S.D. = 0.41).